Metamaterial antenna array fed by distributed Bragg deflector for beam steering on SOI platform - Ginel-Moreno, Pablo; Hadij-El-Houati, Abdelfettah; Sánchez-Postigo, Alejandro; Wanguemert-Pérez, Juan Gonzalo; Molina-Fernández, Íñigo; Schmid, Jens H.; Cheben, Pavel; Ortega-Moñux, Alejandro (My University, 2023)
The capability to radiate collimated steerable beams of light is crucial for many applications, such as remote sensing and free-space optical communications. Here we experimentally demonstrate a novel 1D-antenna array architecture that exhibits a far-field Gaussian profile with an angular divergence of 1.8° × 0.2°.
Keywords: Redes de antenas; Metamateriales; Óptica integrada; Óptica electrónica; Guías de ondas ópticas; Silicon photonics; Integrated optics; Subwavelength gratings; Metamaterials; Near-infrared; Waveguides; Optical antennas; Optical phase arrays